The EFL pre-service teachers' experiences and challenges in designing teaching materials using TPACK framework - Syamdianita Syamdianita; Bambang Yudi Cahyono (Studies in English Language and Education, 2021)
This study aimed to explore the EFL (English as a Foreign Language) pre-service teachers’ experiences in designing and implementing teaching materials by using the Technological Pedagogical Content Knowledge (TPACK) framework through the Learning by Design (LBD) approach. It also identified the challenges faced by the pre-service teachers in designing and implementing the teaching materials. This study involved EFL pre-service teachers in the Province of East Kalimantan, Indonesia. Semi-structured interviews and document analysis were used to gather data needed to accomplish the research objectives. The results of the study showed that the LBD approach was found to be beneficial for the pre-service teachers in designing and implementing teaching materials by using the TPACK framework. The LBD approach helped the pre-service teachers in combining the technological tools and applications with teaching. The EFL pre-service teachers believed that the process that they experienced, enabled them to have a positive change in designing the teaching materials. However, some challenges were still faced by the EFL pre-service teachers in designing and implementing the teaching materials. These included the EFL pre-service teachers’ low level of computer skill, their lack of proficiency in content knowledge, and the availability of media. Moreover, the challenges they faced did not make them afraid of having more experience in LBD activities to promote their abilities in designing teaching materials and in teaching using the materials.